Continuous high dosing of lenalidomide in relapsed, refractory or older newly diagnosed acute myeloid leukemia patients not suitable for other treatment options: results from a phase I study - Hütter-Krönke, Marie-Luise; Schlenk, Richard Friedrich (Haematologica, 2019)
Lenalidomide is an immunomodulatory drug approved for multiple myeloma, relapsed mantle cell lymphoma and myelodysplastic syndrome (MDS) with deletion of chromosome 5q (del(5q)). Based on the high rate of hematologic improvement and cytogenetic responses seen in del(5q) MDS, several trials have been